2008
DOI: 10.1161/hypertensionaha.108.109934
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is Elevated 30 Years After Eclamptic Pregnancy

Abstract: Abstract-Women with a history of preeclampsia or eclampsia (seizure during preeclamptic pregnancy) are at increased risk for cardiovascular disease after pregnancy for reasons that remain unclear. Prospective studies during pregnancy suggest that inflammation, dyslipidemia, and insulin resistance are associated with increased risk of preeclampsia. Elevated serum C-reactive protein (CRP Ͼ3 mg/L) is an indicator of inflammation and cardiovascular risk. We hypothesized that Icelandic postmenopausal women with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…7 It has been suggested that the release of placental debris, microparticles, 8 and molecules secreted into the maternal blood flow might be responsible for the maternal response triggering systemic inflammation, endothelial lesions and subsequent symptoms. 9 In addition, vIUGR can be attributed to a reduction of the vascular flow towards the fetus interfering with the fetal growth.…”
Section: Combination Of Promoter Hypomethylation and Pdx1 Overexpressmentioning
confidence: 99%
“…7 It has been suggested that the release of placental debris, microparticles, 8 and molecules secreted into the maternal blood flow might be responsible for the maternal response triggering systemic inflammation, endothelial lesions and subsequent symptoms. 9 In addition, vIUGR can be attributed to a reduction of the vascular flow towards the fetus interfering with the fetal growth.…”
Section: Combination Of Promoter Hypomethylation and Pdx1 Overexpressmentioning
confidence: 99%
“…From these data, the investigators con-cluded that factors that increase the risk for cardiovascular disease might also be linked to preeclampsia [15]. This was further supported by the finding that classic risk factors for cardiovascular disease in women with a history of preeclampsia including systolic and diastolic blood pressure, body mass index, and concentrations of cholesterol and triglycerides [10,16,17] were increased compared to women with uncomplicated pregnancies. In addition, Blaauw et al [12] found increased intima-media thickness (IMT) of femoral arteries measured by ultrasonography in women who had preeclampsia three months post partum.…”
Section: Discussionmentioning
confidence: 85%
“…These differences are not fully explained by the higher BMI typical of women with a history of GDM. Studies of lipid profiles after pregnancies complicated by preeclampsia are consistent with increased atherogenesis risk, including consistently reported higher total cholesterol, LDL cholesterol, and triglycerides, although these differences are not always statistically significant Manten et al 2007;Hubel et al 2008;Laivuori et al 1996;Magnussen et al 2009;Romundstad et al 2010;Sattar et al 2003;Smith et al 2009). Associations of reduced HDL cholesterol after preeclampsia have been reported by some Magnussen et al 2009;Romundstad et al 2010;Smith et al 2009) but not all (Manten et al 2007;Laivuori et al 1996;Sattar et al 2003) studies.…”
Section: Cardiovascular Risk After Pregnancy Complicationsmentioning
confidence: 97%
“…After pregnancy, plasma C-reactive protein is elevated among women with prior eclampsia and indicated preterm births suggesting that systemic low-grade inflammation may link some adverse pregnancy outcomes and later CVD (Hastie et al 2011b;Hubel et al 2006). Several studies have documented higher C-reactive protein levels among women with a history of GDM (Heitritter et al 2005;Di Cianni et al 2007;Winzer et al 2004).…”
Section: Cardiovascular Risk After Pregnancy Complicationsmentioning
confidence: 99%